Mussels (Mytilus spp.) products authentication: A case study on the Italian market confirms issues in species identification and arises concern on commercial names attribution. (December 2020) - Giusti, A.; Tosi, F.; Tinacci, L.; Guardone, L.; Corti, I.; Arcangeli, G.; Armani, A.
Abstract: In November 2019, the FishLab was consulted by a wholesaler for solving an authentication issue concerning a batch of products labelled as "Chilean mussels" ( Mytilus chilensis ). Samples of the batch had been molecularly identified first as M. chilensis by an external private lab and, subsequently, as Choromytilus chorus through a second analysis entrusted to another external lab by the customer company. The analysis carried out at the FishLab only allowed to identify the samples to genus level ( Mytilus spp.) by sequencing the mitochondrial COI gene. The amplification of the Polyphenolic Adhesive Protein (PAP) gene, a nuclear marker reported as informative for mussel, allowed to suppose the presence of M. chilensis and M. galloprovincialis based on the length of the obtained fragment. In parallel, an in silico analysis of the PAP sequences currently available on GenBank highlighted the lack of the typical mutation point in some sequences of M. galloprovincialis that were identical to those of M. chilensis. Based on a case study investigating mussel products suspected to be mislabelled, this work wants to confirm issues in molecular species identification of Mytilus spp. and highlight concerns on commercial names attribution. Results first confirmed previous scientific community opinion discouraging the use of mtDNA for Mytilus spp. identification due to both its unusual inheritance mechanism and introgression phenomena. The outcomes of the in silico analysis of the PAP sequences called into question the reliability of this marker in discriminating among M. chilensis and M. galloprovincialis . Therefore, also considering the uncertainties of the taxonomic status of these species, a proper re-evaluation process of this marker is needed. However, also the approach one species-one name, currently adopted by the Italian legislator, should be revised for solving labelling issues affecting the market.